FREQUENCY OF FALLS AMONG GERIATRIC POPULATION IN THE TERTIARY CARE HOSPITALS IN PESHAWAR - Fatima, Sana; Saleem, Tehmina; Saleem, Fatima (Annals of Allied Health Sciences, 2024)
Objective: To evaluate the frequency of fall among elderly population in Peshawar. Material & Methods: A cross-sectional study design with a purposive sampling technique was used. The study sample was 280 subjects. The data collection took place in Peshawar and was collected from tertiary care hospitals. A modified questionnaire was used to collect the data. Study duration was 6 months. Results: The study recruited 280 participants results showed 216 (77.1%) reported to experience fall. The most common age group that had fall was between 55-65 years that is 157 out of 280. There was significant association of fall with fracture (P-value0.02). The association of the use of pills with fall was also significant (P-value=0.032). Conclusion: The study concludes that fall is a major problem faced by elderly population. Results in serious injuries and complications and fall are associated with several intrinsic and extrinsic risk factors.